"We Have a Right to Know": Exploring Consumer Opinions on Content, Design and Acceptability of Enhanced Alcohol Labels. (18th September 2017) - Vallance, Kate; Romanovska, Inna; Stockwell, Tim; Hammond, David; Rosella, Laura; Hobin, Erin
Abstract: Aims: This study aimed to refine content and design of an enhanced alcohol label to provide information that best supports informed drinking and to gauge consumer acceptability of enhanced alcohol labels among a subset of consumers. Methods: Five focus groups ( n = 45) were conducted with stakeholders and the general public (age 19+) across one jurisdiction in northern Canada. Interviews were transcribed and analyzed using NVivo software. Results: The majority of participants showed strong support for enhanced alcohol labels with an emphasis on the consumers' right to know about the health risks related to alcohol. Participants preferred larger labels that included standard drink (SD) information, national low-risk drinking guidelines presented as a chart with pictograms, cancer health messaging and a pregnancy warning. Supporting introduction of the labels with a web resource and an educational campaign was also recommended. Conclusions: Displaying enhanced labels on alcohol containers that include SD information, low-risk drinking guidelines and other health messaging in an accessible format may be an effective way to better inform drinkers about their consumption and increase awareness of alcohol-related health risks. Introduction of enhanced labels shows potential for consumer support. Short summary: Focus group findings indicate strong support for enhanced alcohol labels displaying SD information, national drinking guidelines, health messaging and a pregnancy warning. Introduction of enhanced alcohol labels in tandem with an educational campaign may be an effective way to better inform Canadian drinkers and shows potential for consumer support.